English legalese translation into Indonesian - Dewi, Haru Deliana; Wijaya, Andika; Hidayat, Rahayu S. (UI Scholars Hub, 2020)
One of the difficulties in translating English legal texts derives from the uses of specialized language, also known as “legalese“. This research is a preliminary study which sets out to investigate the translation of English legalese into Indonesian in four open-accessed agreements. The data in English, which cover terms and expressions commonly used in legal documents, are classified into seven categories of legal English features. Their Indonesian translations are analysed by using Indonesian dictionaries to discover whether they can be considered as Indonesian legal language. The research finds that most English legalese terms and expressions studied are translated using common words and expressions, which can be looked up in the official monolingual Indonesian dictionary (Kamus Besar Bahasa Indonesia/KBBI) but cannot be found in an Indonesian law dictionary. Therefore, it is concluded that Indonesian legal language is not yet established.